Non‐autonomous overgrowth by oncogenic niche cells: Cellular cooperation and competition in tumorigenesis. Issue 12 (16th October 2015) - Enomoto, Masato; Vaughen, John; Igaki, Tatsushi
Abstract : Tumor progression is classically viewed as the Darwinian evolution of subclones that sequentially acquire genetic mutations and autonomously overproliferate. However, growing evidence suggests that tumor microenvironment and subclone heterogeneity contribute to non‐autonomous tumor progression. Recent Drosophila studies revealed a common mechanism by which clones of genetically altered cells trigger non‐autonomous overgrowth. Such "oncogenic niche cells" (ONCs) do not overgrow but instead stimulate neighbor overgrowth and metastasis. Establishment of ONCs depends on competition and cooperation between heterogeneous cell populations. This review characterizes diverse ONCs identified in Drosophila and describes the genetic basis of non‐autonomous tumor progression. Similar mechanisms may contribute to mammalian cancer progression and recurrence. Abstract : Recent Drosophila studies revealed a common mechanism by which clones of genetically altered cells trigger non‐autonomous overgrowth. Such "oncogenic niche cells" (ONCs) do not overgrow but instead stimulate neighbor overgrowth and metastasis. ONC establishment depends on competition and cooperation between heterogeneous cell populations.